PENGARUH GREEN ACCOUNTING DAN CAPITAL INTENSITY TERHADAP AGRESIFITAS PAJAK : STUDI EMPIRIS PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI NON CYCLICAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Daffa Iqbal Thoriq; Melsanda Damayanti; Rafikul Khairil Yasin; Susilawati Susilawati; Mahwiyah Mahwiyah (Jurnal Ekonomi dan Manajemen, 2025)
This study investigates the effect of green accounting and capital intensity on tax aggressiveness among non-cyclical consumer goods companies listed on the Indonesia Stock Exchange. The research adopts a quantitative approach using secondary data derived from financial reports over a multi-year observation period. The analysis employs panel regression to examine both partial and simultaneous relationships between the variables. The findings reveal that the implementation of green accounting practices does not have a significant impact on reducing tax aggressiveness, indicating that environmental disclosures remain symbolic rather than strategic. In contrast, capital intensity shows a positive and significant relationship, suggesting that firms with greater investment in fixed assets tend to engage in more tax-saving strategies through depreciation. Overall, the results highlight that structural asset composition plays a stronger role in influencing corporate tax behavior than sustainability-related disclosures.